Effect of climatic changes on reproductive performance of Murrah buffaloes in Punjab: A rertrospective analysis - ABAYAWANSA, W D; PRABHAKAR, S; SINGH, A K; BRAR, P S (The Indian Journal of Animal Sciences, 2011)
The present study was conducted to assess the effect of climatic changes on reproductive performance of Murrah buffaloes in Punjab. Retrospective analysis of farm records of 15 years and climatic data on oestrus expression and conception interval revealed that even though buffalo calved and showed postpartum oestrus throughout the year, their seasonal pattern in postpartum oestrus incidence could be due to seasonal changes in climatic factors. Relative humidity, rainfall and vapour pressure had positive influence and air temperature and number of sunshine hours had negative influence on postpartum ovarian activity. Season of calving influenced the intervals from calving to oestrus and conception. Monsoon calving buffalo had shorter while summer and winter calving buffalo had longer intervals from calving to oestrus and conception. Parity order had negative correlations and lactation yield had positive correlations with intervals from calving to oestrus and conception. The interval from calving to oestrus was shorter than the interval from calving to conception across the season of calving, parity order and lactation yield. Therefore, it appears that climatic factors, parity order and lactation yield together with individual animal variations may have influenced the conception. However, this study suggests that further studies are required to elaborate the impact of these factors on postpartum reproductive physiology of buffalo in relation to their hormonal and metabolic environment, ovarian activity, expression of oestrus and conception during the early postpartum period.